Wybrane funkcje administrowania zasobami informatycznymi w przetwarzaniu siatkowym - Owoc, Mieczysław L.; Sachańbiński, Jacek (Chosen Functions of Information Resources Administration in Grid Computing, 2005)
Announced progress of data processing effectiveness in grid technology environment is strictly tied to database administrator's (DBA) functions. The main goal of the paper is to point out key DBA functions can be supported by grid computing and analysis of two of them: monitoring and tunning apart of security. Practical aspects of the problem are presented using Oracle 10g serwer.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 62-71